Assessing ideal teacher’s personality: Students’ perspective and expectations - Nur Hidayah; Afdal Afdal; Nandang Budiman; Husni Hanafi; Mila Yunita (Intelektual Pustaka Media Utama, 2023)
The ideal teacher can reflect on self-development to form a personality that fits the needs of students. Teachers who have achieved a perfect personality figure have a greater chance of success in transferring knowledge and in the student education process. The need for an ideal teacher figure can be a reference for prospective teachers to develop themselves from the beginning of their education. Based on these needs, this study identified the ideal teacher figure based on the student’s perspective. This research design used a survey research design in the quantitative method. The research subjects consisted of 240 students spread across the East Java, Indonesia. The data collection instrument used the student version of the teacher’s personality test. Analysis of the research data was carried out in a statistical-descriptive. The results showed that the four strongest personalities most expected of students were caring, humble, responsible, and patience. Teachers’ ideal personalities help them provide services that align with students’ self-development needs. Suggestions for further research are identifying ideal teacher personalities based on other points of view, including senior teachers, student teacher candidates, and society in general.